Preliminary screening and process standardisation of edible sausage casing from fish viscera - Blossom, K. L.; Thomas, Ancy; Safeena, M. P. (Indian Journal of Fisheries, 2021)
Fish viscera rich in protein components can be utilised for the preparation of sausage casing which will serve as a means of fish processing waste management. A study was conducted on preliminary screening and selection of fish viscera for sausage casing, comparison of the selected casing with goat casing and quality analysis of the sausage during storage at -21Â°C for 60 days. Viscera from Saurida tumbil, Katsuwonus pelamis, Labeo rohita, Pangasius hypophthalmus and Scomberomorus guttatus were collected and salt treated to improve quality. A standard recipe was followed for the preparation of sausage using meat of S. tumbil. Fish sausages were processed at 70Â°C for 15 min. Lizard fish gut was selected as best for sausage casing via sensory analysis and was compared with goat casing by texture profile analyser. There was significant difference in textural qualities except springiness and cohesiveness (p